Pengaruh Pembiayaan Simpan Pinjam Kelompok Perempuan (SPP) Terhadap Pendapatan dalam Peningkatan Ekonomi Masyarakat - Laisa Liza (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2022)
The purpose of this study was to determine the effect of women's group savings and loan financing (SPP) on income in improving the economy of the community in Pidie Regency. This research is quantitative using primary data. The population used in the SPP group in the UPK, Indra Jaya sub-district, Pidie district. It was found that 43 samples would be given a research questionnaire on the economic development of the SPP group in the Indrajaya District. The results showed that there was an effect of group savings and loan financing on income in increasing, as seen from the increase in business that was better than before and an increase in businesses that used to be small to become bigger. far from better economic growth. However, not all of them developed well because some took the business capital given for other needs.